A Census Tract–Level Examination of Differences in Social Determinants of Health Among People With HIV, by Race/Ethnicity and Geography, United States and Puerto Rico, 2017. (March 2022) - Johnson Lyons, Shacara; Gant, Zanetta; Jin, Chan; Dailey, André; Nwangwu-Ike, Ndidi; Satcher Johnson, Anna
Objective: Social and structural factors, referred to as social determinants of health (SDH), create pathways or barriers to equitable sexual health, and information on these factors can provide critical insight into rates of diseases such as HIV. Our objectives were to describe and identify differences, by race/ethnicity and geography, in SDH among adults with HIV. Methods: We conducted an ecological study to explore SDH among people with HIV diagnosed in 2017, by race/ethnicity and geography, at the census-tract level in the United States and Puerto Rico. We defined the least favorable SDH as the following: low income (<40 000 in median annual household income), low levels of education (≥18% of residents have <high school diploma), high levels of poverty (≥19% of residents live below the federal poverty level), unemployment (≥6% of residents in the workface do not have a job), lack of health insurance (≥16% of residents lack health insurance), and vacant housing (≥15% of housing units are vacant). Results: HIV diagnosis rates increased 1.4 to 4.0 times among men and 1.5 to 5.5 times among women as census-tract poverty levels increased, education levels decreased, income decreased, unemployment increased, lack of health insurance increased, and vacant housing increased. Among racial/ethnic groups by region and SDH, we observed higher HIV diagnosis rates per 100 000 population among non-Hispanic Black (49.6) and non-Hispanic White (6.5) adults in the South and among Hispanic/Latino (27.4) adults in the Northeast than in other regions. We observed higher HIV diagnosis rates per 100 000 population among non-Hispanic Black (44.3) and Hispanic/Latino (21.1) adults than among non-Hispanic White (5.1) adults. Conclusion: Our findings highlight the importance of SDH in HIV infection and support the need for effective, targeted local interventions to specific populations based on HIV diagnoses and prevalence to prevent infection and reduce racial/ethnic disparities.